2017
DOI: 10.5897/ijeaps2017.0519
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of job satisfaction on the relationship between teachers perceptions of supervisor support and job performances

Abstract: The main purpose of this study is to examine the relationship between teachers' perceptions of supervisor support and job performances and the mediating role of job satisfaction in this relationship. The study group consists of 206 teachers working in the public high schools in the Giresun province centre during the 2016-2017 academic year. The study group has been determined by simple randomized sampling method. In the study, the effect of teachers' supervisor support perceptions on job performance and the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
3
4
0
Order By: Relevance
“…This study indicates that supervisor support has a significant effect on work performance. It is aligned with research conducted by Talukder & Galang (2021); other studies, such as those conducted Tevfik & Guven (2017), also found that supervisor support significantly affects work performance. Supervisors can reduce high employee stress levels by supporting their efforts to balance work and family responsibilities.…”
Section: Supervisor Support On Job Performancesupporting
confidence: 82%
“…This study indicates that supervisor support has a significant effect on work performance. It is aligned with research conducted by Talukder & Galang (2021); other studies, such as those conducted Tevfik & Guven (2017), also found that supervisor support significantly affects work performance. Supervisors can reduce high employee stress levels by supporting their efforts to balance work and family responsibilities.…”
Section: Supervisor Support On Job Performancesupporting
confidence: 82%
“…The results also confirm that job satisfaction mediated the relationship between the workload and academic staff performance, thus hypothesis 2 was supported. This confirmation establishes job satisfaction as a workload-performance mediator in an academic setting which corresponds to previous suggestions that job satisfaction should be considered as an antecedent of academic performance (Tevfik & Ozdem, 2017). The present study further suggests that academic staff's source of stress primarily comes from workload which influences their satisfaction at work and consequently their performance.…”
Section: Discussionsupporting
confidence: 90%
“…It is thus imperative to design and implement strategies of ensuring that teachers become comfortable at their workplaces. This is because satisfied employees can more effectively fulfill their duties to facilitate achievement of organizational goals (Uzun and Özdem, 2017). According to Koutouzis and Malliara (2017) teachers" job satisfaction is a factor which significantly affects many aspects of quality in education.…”
Section: El-2021-1965mentioning
confidence: 99%